Pembuatan Silase Berbahan Dasar Jerami Tanaman Jagung Sebagai Pakan Ternak Kambing - Umbang Arif Rokhayati (Lembaga Citra Pustaka, 2024)
Silage is forage that is preserved by storing it in an anaerobic silo. This community service (PPM) was conducted in Buladu Village, Kota Barat Subdistrict, Gorontalo Province with the aim of increasing the knowledge and skills of villagers in making silage preserved feed. The method used was demonstration and experimentation, namely giving theory and simulation to target participants, followed by the practice of making silage. Based on the results of observations of the participants' responses from the beginning to the end of the service activities, the silage making training succeeded in increasing the knowledge and skills of goat farmers in Buladu Village.